(3GdeMfbIs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s ((3HdOI JHQjR s)
(3ChdgG (B:s
(3CeG HYO abO SHb dfG bHd cJGHfG gPG CQHYI hYTQhf cJGHkG ai GdMjhGf efgG hYTQhf s
(3BNQgG (B:s
(3hgh Cf JLeY eGA GdcHQjJ heGA GdRFHb heGA GdfhTGOQ agh ai Gdcd hGMO s
(3Vef eLehY , JQJjHgG (B: (3ef U (B167 - (3U(B171s
(3GdfSNI HgG MhGTs
(3hQO cPdc ai Qbe (B96s
(3hgh GdebGdI GdNGeSI hGdYTQhf ef cJGH GdSHYjfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs